Kinase inhibitors reduce 7,12-dimethylbenz[a]anthracene-induced onco-suppressor gene expression in short-term experiments / Inibitori delle chinasi riducono l’espressione genica dell’onco-soppressore indotto da 7,12- dimethylbenz[a]anthracene in esperimenti a breve termine - Gergely, P.; Budán, F.; Szabó, et al., I. (European Journal of Oncology and Environmental Health, 2012)
Aims. Elevated expression of oncogenes and tumour suppressor genes after treatment with 7,12- dimethylbenz[a]anthracene (DMBA) as early markers of carcinogenesis has been previously observed. The potential antineoplastic and chemopreventive properties of four protein tyrosine kinase (PTK) inhibitor molecules were studied. Materials and methods. In order to determine whether a promising antineoplastic activity would extend to anticarcinogenic properties, the effects of these molecules on the 7,12 DMBAinduced expression of Ha-ras oncogene and p53 tumour suppressor genes in the liver, lungs, bone marrow and kidney of CBA/Ca inbred mice was investigated. The experimental molecules were administered (I) 24 hours prior to, (II) simultaneously with, or (III) 24 hours after DMBA exposure. Results. PTK inhibitor (1Z)-1-(3,4-Dihydroxybenzylidene)-3,4-dihydro[1,4]oxazino[3,4-b]quinazolon-6(1H)-on and N-(3-bromophenyl)-6,7-dimethoxy quinazolin-4-amine reduced the expression of Ha-ras and p53 genes in all of the examined organs in the different treated groups. Another two PTK inhibitor, 2-Benzyl-1-(4-hydroxyphenyl)-3-me-thyl-2,3-dihydroimidazo[5,1-b]quinazolin-9(1H)-one and 2-[(2E)-2-(3,4-dihydroxybenzylidene)hydrazino]-N-(3-nitrophenyl)-2-oxoacetamide reduced both Haras and p53 gene expression induced by DMBA in all of the examined organs (except for the kidneys, where only Ha-ras expression decreased) in all of the experimental settings. Conclusions. Our in vivo short-term experimental results provide some evidence, that PTK inhibitors exhibit antineoplastic and chemopreventive effects by reversing the overexpression of the early markers of carcinogenesis. This early molecular biomarker model indicates the first steps of malignant transformation at subcellular level and possible anti-tumour effects, as well. Inibitori delle chinasi riducono l’espressione genica dell’onco-soppressore indotto da 7,12- dimethylbenz[a]anthracene in esperimenti a breve termine Finalità. È stato precedentemente osservato che il trattamento con 7,12- dimethylbenz[a] anthracene (DMBA) induce l’espressione di oncogeni e di geni onco-soppressori, che costituiscono indicatori precoci di carcinogenesi. Il presente studio valuta le potenziali proprietà antineoplastiche e chemiopreventive di quattro inibitori delle proteine tirosin-chinasi (PTK). Materiali e metodi. Per determinare se una potenziale attività antineoplastica di queste molecole sia associata a proprietà anticarcinogeniche, è stato valutato il loro effetto sull’espressione dei geni onco-soppressori Ha-ras e p53, indotta dal DMBA, nel fegato, polmoni, midollo osseo e rene di topi di ceppo CBA/Ca. Le molecole in esame sono state somministrate (I) 24 ore prima, (II) durante, o (III) 24 ore dopo esposizione a DMBA. Risultati. Gli inibitori di PTK (1Z)-1-(3,4-Dihydroxybenzylidene)-3,4-dihydro[1,4]oxazino[3,4-b]quinazolon-6(1H)-uno e N-(3-bromophenyl)-6,7-dimethoxy quinazolin-4-amina hanno ridotto l’espressione dei geni Ha-ras e p53 in tutti gli organi esaminati e per tutti gli schemi di somministrazione. Altri due inbitori di PTK, 2-Benzyl-1-(4-hydroxyphenyl)-3-methyl-2,3-dihydroimidazo[5,1-b]quinazolin-9(1H)-uno e 2-[(2E)-2-(3,4-dihydroxybenzylidene) hydrazino]-N-(3-nitrophenyl)-2-oxoacetamide, hanno ridotto l’espressione dei geni Ha-ras e p53 indotta da DMBA in tutti gli organi esaminati (eccetto il rene, dove solo l’espressione di Ha-ras è diminuita). Conclusioni. I nostri risultati, concernenti la somministrazione a breve termine in vivo, forniscono una qualche evidenza circa un effetto antineoplastico e chemiopreventivo degli inibitori delle PTK prevenendo la sovra-espressione di indicatori precoci di carcinogenesi. Questo modello di bioindicatori molecolari precoci è indice dei primi stadi di trasformazione maligna a livello subcellulare, nonchè possibili effetti antitumorali.